Anteseden Jiwa Kepemimpinan dan Tanggung Jawab Siswa dalam Kegiatan Pramuka : Analisis Penyelenggaraan Kegiatan Pramuka pada Sekolah Dasar - Sri Wahyuni; Denny Puspa; Halim Sugeng; Satrio Budiyanto; Achmad Daengs GS (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Character education is a fundamental foundation in developing high-quality human resources, particularly in fostering leadership spirit and responsibility. However, in reality, the leadership spirit and responsibility of students at Elementary School X are still not optimal. Therefore, the school, through scouting (Pramuka) activities, seeks to improve character education in these aspects. This study aims to analyze the effect of scouting activities on students’ leadership spirit and responsibility at Elementary School X. This research employs a quantitative method with a causal approach. The population consists of students at Elementary School X. The sample size was determined using the Hair et al. (2014) formula; with 14 indicators, a total of 60 students were selected as the sample. Data were collected through questionnaires and analyzed using Partial Least Square (PLS). The results show that scouting activities have a significant positive effect on students’ leadership spirit and responsibility. Therefore, scouting activities can be considered an effective character education strategy in developing leadership spirit and responsibility among elementary school students.